Characterization of Nd(Tb)-Fe-B Based Exchange Spring Nanocomposite Magnets. Issue 2 (15th April 2019) - Karmaker, Palash Chandra; Rahman, Md Obaidur; Dan, Nguyen Huy; Liba, Samia Islam; Nordblad, Per; Hoque, Sheikh Manjura
Abstract : We attempt to optimize the composition for the performance of R2 Fe14 B/Fe3 B based hard nanocomposite alloys with R=Nd and Tb by optimizing phases in order to develop hysteresis parameters such as maximum magnetization, coercivity and maximum energy product with the variation of composition and heat treatment. The samples were prepared from arc-melted ingot of different compositions. The crystallization temperatures were obtained from the differential scanning calorimeter (DSC) traces of the samples with composition of Nd4-x Tbx Fe71 Co5 Cu0.5 Nb1 B18.5 (x = 0, 0.2, 0.4, 0.6, 0.8 and 1). According to the crystallization temperatures, the samples were annealed at 600°C, 625°C, 650°C, 675°C and 700°C for 10 min. Amorphosity and crystallization behavior was studied by X-ray diffraction using CuKα radiation (1.5418 Å). The Mössbauer spectra of all the samples were recorded at room temperature by using 57 Fe Mössbauer spectrometry in transmission geometry with constant acceleration spectrometer. Magnetic properties were determined by vibrating sample magnetometer (VSM) in the as-cast and annealed condition. Though the highest value of coercivity (Hc ) and remanent ratio (Mr /Ms ) were found to be 4.18 kOe and 0.72 for the sample of composition Nd3 Tb1 Fe71 Co5 Cu0.5 Nb1 B18.5 annealed at 650°C with higher concentration of Tb, the maximum energy product (BH)max was determined to be 12.67 MGOe for the sample of Nd3.8 Tb0.2 Fe71 Co5 Cu0.5 Nb1 B18.5 .